Comparison of microstructure and chemical composition of hydroxyapatite and fluorapatite coatings deposited on Ti-6Al-4V substrates by Nd-YAG laser. (May 2015) - Chien, C. S.; Kuo, T. Y.; Liu, C. W.; Lin, H. C.; Liao, T. Y.; Hong, T. F.; Lee, T. M.
<x content-type="archive" xml:space="preserve">Abstract</x> In this paper, hydroxyapatite or fluorapatite, was clad on the Ti-6Al-4V substrate by Nd-YAG laser technology, respectively. Scanning electron microscopy, energy dispersive X-ray spectrometry, X-ray diffraction were utilised to compare the differences of microstructures, chemical compositions and the compounds in the coating layer and transition layer of samples. The results show that CaTiO3, TiO2, Al2O3 and Ca2P2O7 are compounds in the coating layer of hydroxyapatite cladding sample, and CaTiO3 is the main phase which appears a dendrite-like structure feature. Besides, the dendrite-like CaTiO3 phase, few compounds of TiO2, Al2O3 and the granular residual FA were found that dispersed between interdendritic areas in the coating layer of fluorapatite cladding sample. Compared with these hydroxyapatite and fluorapatite cladding samples, the distribution feature of elements Ca, P, Ti in the coating layer and transition layer is similar, but relatively higher amount of Ca, P and lower Ca/P ratio were found in the coating layer of fluorapatite cladding sample.